2020
DOI: 10.1111/jcmm.14936
|View full text |Cite
|
Sign up to set email alerts
|

Isoalantolactone restores the sensitivity of gram‐negative Enterobacteriaceae carrying MCR‐1 to carbapenems

Abstract: Polymyxin B has been re‐applied to the clinic as the final choice for the treatment of multidrug‐resistant gram‐negative pathogenic infections, but the use of polymyxin B has been re‐assessed because of the emergence and spread of the plasmid‐mediated mcr‐1 gene. The purpose of this study was to search for an MCR inhibitor synergistically acting with polymyxin to treat the infection caused by this pathogen. In this study, we used the broth microdilution checkerboard method to evaluate the synergistic effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Furthermore, it could be shown that low micromolecular concentrations (1–20 µM) of ALT intensified the uptake of S. aureus and thus stimulated immune functions of macrophages [ 185 ]. However, IAL has also recently been found to exert strong synergistic effects with carbapenems (polymyxin B or colistin) in the treatment of mcr-1-positive Enterobacteriaceae such as K. pneumoniae and E. coli in vivo and in vitro [ 186 ].…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…Furthermore, it could be shown that low micromolecular concentrations (1–20 µM) of ALT intensified the uptake of S. aureus and thus stimulated immune functions of macrophages [ 185 ]. However, IAL has also recently been found to exert strong synergistic effects with carbapenems (polymyxin B or colistin) in the treatment of mcr-1-positive Enterobacteriaceae such as K. pneumoniae and E. coli in vivo and in vitro [ 186 ].…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…Natural/organic compounds identified with a synergistic effect on colistin include Honokiol 186 , Isoalantolactone (IAL) 187 , Calycosin 188 and Eugenol 189 . Honokiol was derived from the dry skin and bark of Magnolia officinalis 186 , IAL is the main sesquiterpene lactone from Radix inulae and other plants 187 , Calycosin is a flavonoid from a direct root extract of the traditional Chinese medicinal herb, Radix astragali.…”
Section: Discussionmentioning
confidence: 99%
“…Other novel compounds that have been reported to restore susceptibility of polymyxins in mcr-1 producing isolates includes the novel MCR-1 inhibitor, Osthole Natural/organic compounds identified with a synergistic effect on colistin include Honokiol 186 , Isoalantolactone (IAL) 187 , Calycosin 188 and Eugenol 189 . Honokiol was derived from the dry skin and bark of Magnolia officinalis 186 , IAL is the main sesquiterpene lactone from Radix inulae and other plants 187 , Calycosin is a flavonoid from a direct root extract of the traditional Chinese medicinal herb, Radix astragali. 188 Lastly, Eugenol is a phenylpropanoid, an essential oil isolated from plants 190 .…”
Section: Natural Compoundsmentioning
confidence: 99%
“…2020) (Lu et al . 2020). As for toxicity determination in vivo , the mice ( n = 9) were intraperitoneally injected with 30 mg kg −1 of polymyxin B or STK‐35/66 and observed for consecutive 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…and 10 mg kg −1 polymyxin B (subcutaneously, s.c.) were administered as the vehicle and positive groups, respectively. The survival of infected mice was monitored twice a day for seven consecutive days (She et al 2020) (Lu et al 2020). As for toxicity determination in vivo, the mice (n = 9) were intraperitoneally injected with 30 mg kg −1 of polymyxin B or STK-35/66 and observed for consecutive 7 days.…”
Section: Survival Curve Determinationmentioning
confidence: 99%